Advanced Maintenance Modelling for Asset Management Techniques and Methods for Complex Industrial Systems - Crespo Márquez, Adolfo; González-Prida Díaz, Vicente; Gómez Fernández, Juan Francisco (Springer International Publishing : Imprint: Springer, 2018)
This book promotes and describes the application of objective and effective decision making in asset management based on mathematical models and practical techniques that can be easily implemented in organizations. This comprehensive and timely publication will be an essential reference source, building on available literature in the field of asset management while laying the groundwork for further research breakthroughs in this field. The text provides the resources necessary for managers, technology developers, scientists and engineers to adopt and implement better decision making based on models and techniques that contribute to recognizing risks and uncertainties and, in general terms, to the important role of asset management to increase competitiveness in organizations.